Human and Canine Pulmonary Blastomycosis, North Carolina, 2001–2002 - MacDonald, Pia D.M. (Centers for Disease Control and Prevention, 2006)
We investigated a cluster of blastomycosis in 8 humans and 4 dogs in a rural North Carolina community. Delayed diagnosis, difficulty isolating Blastomyces dermatitidis in nature, and lack of a sensitive and specific test to assess exposure make outbreaks of this disease difficult to study.